PERAN KELUARGA DALAM PENDIDIKAN ANAK USIA DINI - FAHRUDDIN, FAHRUDDIN (PPs UNJ, 2011)
Family is an informal education that is essential for early childhood education, the integrity of a family, especially mother and father very much needed so that what parents strived to help children internalize the moral values, perceived as a relief to be recognized and understood, precipitated, and personalized in child. children who feel the unity in the family to bear the understanding of the world